Genetic diversity of North American captive-born gorillas (Gorilla gorilla gorilla) - Simons, Noah D (Blackwell Publishing Ltd, 2013)
Western lowland gorillas (Gorilla gorilla gorilla) are designated as critically endangered and wild populations are dramatically declining as a result of habitat destruction, fragmentation, diseases (e.g., Ebola) and the illegal bushmeat trade. As wild populations continue to decline, the genetic management of the North American captive western lowland gorilla population will be an important component of the long-term conservation of the species. We genotyped 26 individuals from the North American captive gorilla collection at 11 autosomal microsatellite loci in order to compare levels of genetic diversity to wild populations, investigate genetic signatures of a population bottleneck and identify the genetic structure of the captive-born population. Captive gorillas had significantly higher levels of allelic diversity (t(7) = 4.49, P = 0.002) and heterozygosity (t(7) = 4.15, P = 0.004) than comparative wild populations, yet the population has lost significant allelic diversity while in captivity when compared to founders (t(7) = 2.44, P = 0.04). Analyses suggested no genetic evidence for a population bottleneck of the captive population. Genetic structure results supported the management of North American captive gorillas as a single population. Our results highlight the utility of genetic management approaches for endangered nonhuman primate species.